Development and Tryout of Value-based Module for Value Inculcation - Srivastava, Sujata (JOURNAL OF INDIAN EDUCATION, 2020)
The impact of modernity can be felt on development and progress, in the process, creating a culture of materialism. The youth today is involved in murder, shooting, loot, rape, stabbing in cold blood. Value education in schools can take care of value degradation rampant in India and globally. The objectives of the study were to develop, implement and study the effectiveness of the value-based module for teaching English in terms of conceptual knowledge and value perception in the values of Love, Compassion and Helpfulness along with achievement. Quasi experimental research design was used in this research. Convenience sampling technique was followed to select the sample which consisted of 20 students each from Class IX of two schools of Vadodara city. Achievement test, value knowledge test and value perception scale were constructed and administered to gather the data. The study was conducted in five phases. Mean, SD, Mann-Whitney U-test was used for data analysis. The findings revealed that the module developed for teachers for inculcation of values in students through teaching of English was effective as the students had a higher conceptual knowledge and a higher value perception of the values of love, compassion and helpfulness, however no difference was found in the achievement in English.